Endothelial Cells Expressing Endothelial and Mesenchymal Cell Gene Products in Lung Tissue From Patients With Systemic Sclerosis–Associated Interstitial Lung Disease - Mendoza, Fabian A.; Piera‐Velazquez, Sonsoles; Farber, John L.; Feghali‐Bostwick, Carol; Jiménez, Sergio A. (Arthritis & rheumatology (Hoboken, N.J.), 2016)
Objective To examine whether lung endothelial cells (ECs) from patients with systemic sclerosis (SSc)–associated interstitial lung disease (ILD) express mesenchymal cell–specific proteins and gene transcripts, indicative of the occurrence of endothelial‐to‐mesenchymal phenotypic transition (EndoMT). Methods Lung tissue from 6 patients with SSc‐associated pulmonary fibrosis was examined by histopathology and immunohistochemistry. Confocal laser microscopy was utilized to assess the simultaneous expression of EC and myofibroblast molecular markers. CD31+CD102+ ECs were isolated from the lung tissue of 2 patients with SSc‐associated ILD and 2 normal control subjects, and the expression of EC and mesenchymal cell markers and other relevant genes was analyzed by quantitative polymerase chain reaction, immunofluorescence microscopy, and Western blotting. Results Immunohistochemical staining revealed cells expressing the EC‐specific marker CD31 in the subendothelial, perivascular, and parenchymal regions of the lungs from all SSc patients. Confocal microscopy identified cells displaying simultaneous expression of von Willebrand factor and α‐smooth muscle actin in small and medium‐sized arterioles in the SSc lung tissue but not in normal control lungs. CD31+CD102+ ECs isolated from SSc lungs expressed high levels of mesenchymal cell–specific genes (type I collagen, type III collagen, and fibronectin), EC‐specific genes (type IV collagen and VE‐cadherin), profibrotic genes (transforming growth factor β1 and connective tissue growth factor), and genes encoding EndoMT‐related transcription factors (TWIST1 and SNAI2). Conclusion Cells coexpressing EC‐ and mesenchymal cell–specific molecules are present in the lungs of patients with SSc‐associated ILD. CD31+CD102+ ECs isolated from SSc lungs simultaneously expressed mesenchymal cell– and EC‐specific transcripts and proteins. Collectively, these observations demonstrate the occurrence of EndoMT in the lungs of patients with SSc‐associated ILD.